THE PROBLEMATIC OF ACCESS TO SUPERIOR EDUCATION. AN APPROACH TO THE CUBAN REALITY - Haramboure Gómez, Raisa (2014)
The following article involves more than 20 years experience in the direction of accessing the Higher Education in Cuba, based on the most outstanding international cases. We analyse the main functions, models and many other important topics that rule the access to universities.